Genetic diversity of red and black upland rice accessions from East Nusa Tenggara, Indonesia as revealed by agro-morphological characters - YOSEP S. MAU; JENNY E.R. MARKUS; SHIRLY SHIRLY; S. OEMATAN; A. S.S. NDIWA; DODY D. HANDOKO; ANGGIANI NASUTION; KISMAN MAKBUL (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Mau YS, Markus JER, Shirly, Oematan S, Ndiwa ASS, Handoko DD, Nasution A, Makbul K. 2017. Genetic diversity of red and black upland rice accessions from East Nusa Tenggara, Indonesia as revealed by agro-morphological characters. Biodiversitas 18: 197-211. A number of upland red and black rice accessions were collected from various locations of East Nusa Tenggara Province, Indonesia. This germplasm collection is invaluable genetic resource that can be utilized to generate new improved varieties. The objective of the present study was to elucidate genetic diversity of the rice germplasm based on agro-morphological characters. The study was carried out in the Glasshouse involving 40 upland red and black rice accessions. Observed variables included qualitative and quantitative agro-morphological characters. A total of 26 qualitative and 16 quantitative characters were observed. Qualitative characters were descriptively analyzed while quantitative characters were subjected to analysis of variance. Both data were also subjected to cluster analysis. Research results revealed a significant difference among rice accessions in both qualitative and quantitative characters. The tested rice accessions exhibited substantial differences in most of the observed qualitative and quantitative variables. Cluster analysis employing qualitative variables classified the rice accessions into 4 clusters and 15 sub-clusters. The same analysis using quantitative characters placed the 40 rice accessions into 5 clusters and 8 sub-clusters. Evaluation of agro-morphological characters demonstrated that the rice germplasm under the present study possessed a high genetic diversity. Keywords: upland rice, agro-morphology, characters, diversity